IMPLEMENTATION OF HARMONIZING, FINISHING AND STRENGTHENING THE CONCEPT OF LAW DESIGN WITH PANCASILA VALUES: PELAKSANAAN PENGHARMONISASIAN, PEMBULATAN DAN PEMANTAPAN KONSEPSI RANCANGAN UNDANG-UNDANG DENGAN NILAI-NILAI PANCASILA - Basuki Kurniawan; Rohmad Agus Sholihin; Nita Ryan Purbosari (Constitutional Law Society, 2022)
Harmonizing the conception of draft laws is a process that must be carried out in the formation of laws and regulations, especially at the drafting stage. The aim is to harmonize with Pancasila, the 1945 Constitution of the Republic of Indonesia and other laws and drafting techniques as well as to produce agreement on the regulated substance so that it becomes a statutory regulation which is a unified whole within the framework of the national legal system. In practice, the harmonization of the draft law concept has not been harmonized with the values ​​of Pancasila. Whereas in terms of legal dogmatics and legal theory, the draft law must be harmonized with the values of Pancasila.